Occurrence of qnr Gene in Diarrheagenic Ciprofloxacin¬-Resistant Escherichia coli Isolated from Patients with Acute Diarrhea - Thanaa R. Abdulrahman (Journal of Global Pharma Technology, 2020)
Background: Quinolone resistance Escherichia coli have been dramatically increased in last years. This resistance occurs either by chromosomal, or plasmid-mediated. The plasmid-mediated Quinolone resistance (qnr) gene which encompasses five different groups including qnrA, qnrB, qnrC, qnrD, and qnrS has been shown to aid resistance to fluoroquinolones. Objective: To estimate the occurrence of qnr among Diarrheagenic E coli strains isolated from patients with acute diarrhea. Methods: This study included 43 E. coli clinical isolates recovered from 304 fresh stool specimens which were collected from patients presenting with acute diarrhea. Stool samples were plated onto MacConkey agar for 24 hr at 37ºC. The susceptibility and resistance to Ciprofloxacin and Nalidixic acid for all bacterial isolates were identified by standard procedures such as disk diffusion test and minimum inhibitory concentration. DNA was extracted from plasmids using commercial kits and then, the molecular diagnosis was performed with Multi-Plex polymerase chain reaction (PCR) technique using specific primers for qnr genes. Results: Culture result revealed that E. coli was isolated from 43(14.1%) of 304 stool samples. Among these, 12 isolates were resistant to both nalidixic acid and ciprofloxacin. There were 18 qnr genes among these isolates. The qnrA gene was the most common (8/18, 44.4%) followed by qnrB (6/18, 33.3%), whereas qnrS gene represented only 4/18 (22.2%) of the total gens. Conclusion: there is an increase in the occurrence of quinolone resistance among Diarrheagenic E. coli which harbored multiple plasmids profile. The most common gene for quinolone resistance in current study was qnrA gene.Keywords: Diarrheagenic Escherichia coli, Quinolone resistance (qnr) genes, Ciprofloxacin, Nalidixic acid.